Building Psychological Resilience in Cancer Patients: A Systematic Review of Internal–External Factors and Intervention Effectiveness - Dewa Gede Firstia Wirabrata; Wulanyani Ni Made Swasti (Department of Guidance and Counseling, FIP, Undiksha, 2026)
Psychological resilience is the ability to adapt and recover from cancer-related stress. However, studies on its factors and psychosocial interventions remain conceptually and empirically inconsistent. This study aimed to analyze the conceptual framework of resilience, explore the internal and external factors influencing resilience in adult cancer patients, and evaluate the effectiveness of resilience-based psychosocial interventions. This study employed a systematic review method based on the PRISMA guidelines. The subjects of the study consisted of scientific articles discussing resilience among adult cancer patients. Data were collected through literature searches in reputable scientific databases and analyzed using narrative synthesis through systematic processes of study selection, data extraction, and quality appraisal. The findings revealed that resilience is influenced by internal factors, including hope, optimism, self-efficacy, emotional regulation, spirituality, and adaptive coping strategies, as well as external factors such as social support, clinical conditions, and psychosocial services. Mindfulness-based interventions, cognitive behavioral therapy, acceptance and commitment therapy, meaning-centered therapy, and coping-skills training were found to reduce psychological distress and improve patients’ quality of life. The study concludes that resilience in cancer patients is dynamic and develops through the interaction of psychological, social, spiritual, and clinical factors. The implications of this study emphasize the importance of integrating resilience assessment and resilience-oriented psychosocial services into healthcare practices to support the long-term psychological well-being of cancer patients.